β-Perfluoroalkylated meso-Aryl-Substituted Subporphyrins: Synthesis and Properties - Zhao, Shuai; Liu, Chao; Guo, Yong; Xiao, Ji-Chang; Chen, Qing-Yun (Synthesis, 2014)
A convenient and effective synthesis of various novel β-perfluoroalkylated subporphyrins has been developed. β-Trifluoromethylated subporphyrins were efficiently synthesized by the reaction of brominated subporphyrins with FSO2CF2CO2Me/CuI [with or without Pd(dba)2]. Potentially valuable β-perfluoroalkylated, β-monotetrafluorobenzo, and β-monotrifluorobenzo subporphyrins were successfully obtained by a modified sulfinatodehalogenation reaction. Photophysical and electrochemical studies on several typical perfluoroalkylated subporphyrins demonstrated that β-hexakistrifluoromethylated subporphyrins show an obviously red-shifted UV/Vis absorption band that arises from macrocycle nonplanar distortion induced by trifluoromethyl groups, but this distortion is not so severe as that of the corresponding β-octakis(trifluoromethyl)-meso-tetraphenylporphyrin. This was supported by their redox potential data. In addition, β-monotrifluorobenzo subporphyrin exhibits a special fluorescence spectrum of vibronic structure.
Keywords: subporphyrin; palladium; perfluoroalkyl; trifluoromethylation; sulfinatodehalogenation